Characteristics, treatment and in-hospital outcomes of patients with STEMI in a metropolitan area of a developing country: an initial report of the extended Jakarta Acute Coronary Syndrome registry. Issue 8 (31st August 2016) - Dharma, Surya; Andriantoro, Hananto; Purnawan, Ismi; Dakota, Iwan; Basalamah, Faris; Hartono, Beny; Rasmin, Ronaly; Isnanijah, Herawati; Yamin, Muhammad; Wijaya, Ika Prasetya; Pratama, Vireza; Gunawan, Tjatur Bagus; et al.
Abstract : Objective: We studied the characteristics of patients with ST segment elevation myocardial infarction (STEMI) after expansion of a STEMI registry as part of the STEMI network programme in a metropolitan city and the surrounding area covering ∼26 million inhabitants. Design: Retrospective cohort study. Setting: Emergency department of 56 health centres. Participants: 3015 patients with acute coronary syndrome, of which 1024 patients had STEMI. Main outcome measure: Characteristics of reperfusion therapy. Results: The majority of patients with STEMI (81%; N=826) were admitted to six academic percutaneous coronary intervention (PCI) centres. PCI centres received patients predominantly (56%; N=514) from a transfer process. The proportion of patients receiving acute reperfusion therapy was higher than non-reperfused patients (54% vs 46%, p<0.001), and primary PCI was the most common method of reperfusion (86%). The mean door-to-device (DTD) time was 102±68 min. In-hospital mortality of non-reperfused patients was higher than patients receiving primary PCI or fibrinolytic therapy (9.1% vs 3.2% vs 3.8%, p<0.001). Compared with non-academic PCI centres, patients with STEMI admitted to academic PCI centres who underwent primary PCI had shorter mean DTD time (96±44 min vs 140±151 min, p<0.001), higher use of manual thrombectomy (60.2% vs13.8%, p<0.001) and drug-eluting stent implantation (87% vs 69%, p=0.001), but had similar use of radial approach and intra-aortic balloon pump (55.7% vs 67.2%, and 2.2% vs 3.4%, respectively). In patients transferred for primary PCI, TIMI risk score ≥4 on presentation was associated with a prolonged door-in to door-out (DI-DO) time (adjusted OR 2.08; 95% CI 1.09 to 3.95, p=0.02). Conclusions: In the expanded JAC registry, a higher proportion of patients with STEMI received reperfusion therapy, but 46% still did not. In developing countries, focusing the prehospital care in the network should be a major focus of care to improve the DI-DO time along with improvement of DTD time at PCI centres. Trial registration number: NCT02319473.